Technical and economic substantiation of enclosing constructions of apartment houses - Abashkina, K. (Ways to Improve Construction Efficiency, 2018)
The article is devoted to the actual problem of energy saving and heat conservation. One of the most effective ways of solving this problem is to reduce the cost of heat through the protective structures of buildings and structures. The following variants of fencing constructions of a residential 14-storey building are considered: ceramic block, full brick and aerated concrete with different heaters. Justifies the selection of the most effective option.